Cardioprotective Roles of Endothelial Progenitor Cell-Derived Exosomes - Zeng, Cai-Yu; Xu, Jia; Liu, Xin; Lu, Yuan-Qiang (Frontiers in Cardiovascular Medicine, 2021)
With the globally increasing prevalence, cardiovascular diseases (CVDs) have become the leading cause of mortality. The transplantation of endothelial progenitor cells (EPCs) holds a great promise due to their potential for vasculogenesis, angiogenesis, and protective cytokine release, whose mechanisms are essential for CVD therapies. In reality, many investigations have attributed the therapeutic effects of EPC transplantation to the secretion of paracrine factors rather than the differentiation function. Of note, previous studies have suggested that EPCs could also release exosomes (diameter range of 30–150 nm), which carry various lipids and proteins and are abundant in microRNAs. The EPC-derived exosomes (EPC-EXs) were reported to act on the heart and blood vessels and were implicated in anti-inflammation, anti-oxidation, anti-apoptosis, the inhibition of endothelial-to-mesenchymal transition (EndMT), and cardiac fibrosis, as well as anti-vascular remodeling and angiogenesis, which were considered as protective effects against CVDs. In this review, we summarize the current knowledge on using EPC-EXs as therapeutic agents and provide a detailed description of their identified mechanisms of action to promote the prognosis of CVDs.